Environmental and endogenous drivers of tree mast production and synchrony in piñon–juniper–oak woodlands of New Mexico. Issue 8 (2nd August 2018) - Parmenter, Robert R.; Zlotin, Roman I.; Moore, Douglas I.; Myers, Orrin B.
Abstract: Tree masting (synchronous, episodic reproduction) is common worldwide and is hypothesized to be especially important in ecosystems with low species diversity and productivity as in semi‐arid woodlands of the American Southwest. We analyzed mast dynamics of three dominant tree species, one‐seed juniper (Cupressaceae: Juniperus monosperma ), two‐needle piñon pine (Pinaceae: Pinus edulis ), and Sonoran scrub oak (Fagaceae: Quercus turbinella ), on six sites during 1997–2016 within the Sevilleta National Wildlife Refuge, New Mexico. We tested multiple hypotheses regarding environmental and endogenous variables as controlling mechanisms, analyzing time‐series mast production data in relation to weather variables (precipitation, temperature, relative humidity, vapor pressure deficit, wind) over different time frames, and assessed evidence for weather tracking, resource switching, resource depletion, resource cycling, and pollen limitation. We found that (1) in univariate regression analyses, mast production in all three species was inversely related to lagged late‐summer/autumn temperatures during fruit primordia formation (1‐yr lag for juniper and oak, 2‐yr lag for piñon pine). Juniper mast production ( n  = 412 trees) was positively related to current‐year late‐winter (February–April) precipitation, combined with a negative relationship with current‐year summer temperatures. Piñon pine mast production ( n  = 210 trees) was positively related to 1‐yr lagged total annual precipitation and negatively associated with current‐year spring and summer temperatures. Oak mast production ( n  = 194 trees) also was positively related to current‐year late‐winter precipitation but was not affected by subsequent summer temperatures. (2) Multivariate environmental logistic regression models produced reasonable fits to observed field mast values. (3) High‐mast years in juniper and oak were characterized by greater proportions of trees producing mast and increased mast production per tree. (4) Juniper, oak, and piñon pine mast years were highly synchronized. (5) We found indirect support for resource depletion in all three species at some sites and indirect support for resource cycling in oak populations. (6) We observed only marginal indirect evidence for resource switching in piñon pine and oak. (7) Analyses of atmospheric pollen abundance relative to mast production produced no significant relationships. Predictive models of mast production have direct applications to regional silviculture, wildlife management, and ecosystem services in Southwestern woodlands.